Pengembangan Kapasitas Sumber Daya Manusia (SDM) Pada Sekretariat Daerah Kabupaten Malang - Agustinus Koko Budi Setiawan (Jurnal Administrasi Publik, 2016)
Abstract: Capacity Building Of Human Reseurces (HR) At The Malang District Secretariat Poor. Regional Secretariat District Malang is an institution that helps the Regent in formulating policies and coordinating agencies and regional and technical institutes Regions, while the duties and functions is to conduct capacity building of personnel employees so that the objective of this study was intended to examine the implementation of capacity building of human resources (HR) that of the Regional Secretariat Malang and to describe the obstacles in the implementation of capacity building. This research is a descriptive study using a qualitative approach to data analysis siedel models. The results of this study indicate that the implementation of capacity development of human resources (HR) by the government especially in the Malang regency Regional Secretariat Malang regency has served optimally, but the implementation is still influenced by a number of supporting factors and obstacles faced by the Regional Secretariat Malang. Keyword: Capacity building, Performance of employees, HR Abstrak: Pengembangan Kapasitas Sumber Daya Manusia (SDM) Pada Sekretariat Daerah Kabupaten Malang. Setda Kabupaten Malang merupakan suatu instansi yang membantu Bupati dalam menyusun kebijakan dan mengkoordinasikan dinas dan Daerah dan lembaga teknis Daerah, adapun tugas dan fungsinya ialah melaksanakan peningkatan kapasitas aparatur pegawainya sehingga tujuan dilakukannya penelitian ini dimaksudkan untuk mengetahui  pelaksanaan pengembangan kapasitas sumber daya manusia (SDM) yang ada pada Sekretariat Daerah  Kabupaten Malang dan untuk mendeskripsikan hambatan dalam pelaksanaan pengembangan kapasitas SDM. Penelitian ini merupakan penelitian deskriptif pendekatan kualitatif dengan menggunakan analisis data model siedel . Hasil  penelitian ini menunjukkan bahwa pelaksanaan pengembangan kapasitas sumber daya manusia (SDM) yang dilakukan pemerintah Kabupaten Malang khususnya pada Setda Kabupaten Malang telah berperan secara optimal, tetapi dalam pelaksanaan masih dipengaruhi oleh beberapa faktor pendukung dan penghambat yang dihadapi Setda Kabupaten Malang .   Kata kunci:Pengembangan kapasitas, Kinerja pegawai, SDM